Transcatheter closure of persistent ductus arteriosus in infants using the Amplatzer duct occluder. Issue 4 (1st October 2001) - Fischer, G; Stieh, J; Uebing, A; Grabitz, R; Kramer, H H
Abstract : AIM: To evaluate whether transcatheter closure with the Amplatzer duct occluder offers an alternative to surgical treatment in infants with a persistent ductus arteriosus. METHODS: 12 patients under 1 year of age (age 1–11 months, body weight 2.6–8.7 kg) with clinical and echocardiographic findings of a significant duct were considered for transcatheter closure with the Amplatzer occluder. The device is made of a Nitinol and polyester fabric mesh and provides occlusion by stenting the duct. Measured angiographically, the narrowest diameter of the ducts ranged from 1.5–5 mm; in six patients pulmonary hypertension was also present. RESULTS: The devices were implanted and complete duct occlusion was demonstrated during follow up in 10 patients. Procedure related difficulties occurred in nine of the 12 cases and led to relatively long procedure and fluoroscopy times (procedure time 50–180 minutes, median 80 minutes; fluoroscopy time 4.9–49 minutes, median 16 minutes). In two infants transcatheter closure could not be achieved and surgical duct ligation had to be carried out. CONCLUSIONS: In small infants with a persistent ductus arteriosus the Amplatzer duct occluder offers an alternative to surgical treatment, but further improvement of the implantation system is necessary before the procedure can be recommended as the treatment of choice.